2019
DOI: 10.1177/0734242x19878496
|View full text |Cite
|
Sign up to set email alerts
|

Assessing impact of risk perception and environmental regulation on household carcass waste recycling behaviour in China

Abstract: Carcass waste recycling exerts an important influence on preventing epidemic diseases, improving the ecological environment, and promoting sustainable development of the livestock industry although it has rarely aroused widespread attention throughout the world. Based on the data of 470 households engaged in breeding pigs in Hebei, Henan, and Hubei, China, and considering dead pigs as an example, this study employed the Double Hurdle model to assess impact of risk perception on household dead pig recycling beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…In other words, only when the inhibitory effect of health risk perception is higher than the promotion effect of risk preference, the environmental exposure of women breeders may be at a lower degree. Consistent with the findings of Bryan and Kandulu (2011) and Si et al (2020), who considered that risk perception could enable farmers to strengthen risk management and implement risk intervention by evaluating the degree of risk damage, calculating the ratio of cost-benefit, and measuring the margin and expected utility. Suppose women breeders' health risk perception is higher.…”
Section: Discussion Of Empirical Resultssupporting
confidence: 62%
See 4 more Smart Citations
“…In other words, only when the inhibitory effect of health risk perception is higher than the promotion effect of risk preference, the environmental exposure of women breeders may be at a lower degree. Consistent with the findings of Bryan and Kandulu (2011) and Si et al (2020), who considered that risk perception could enable farmers to strengthen risk management and implement risk intervention by evaluating the degree of risk damage, calculating the ratio of cost-benefit, and measuring the margin and expected utility. Suppose women breeders' health risk perception is higher.…”
Section: Discussion Of Empirical Resultssupporting
confidence: 62%
“…Hence, although women breeders probably allow manure pollution and don't dispose of it harmlessly, they still can enhance the level of health risk perception through communication with other breeders, news media, or government agendas. The high cost of manure cycling, the weak incentive of government support, and the concealment of risk realization make health risk perception vulnerable and drive individuals' towards environmental pollution (Si et al, 2020). Our research showed that a higher degree of risk preference has become a key determinant of rural women breeders' exposure to severe LPM pollution.…”
Section: Discussion Of Empirical Resultsmentioning
confidence: 82%
See 3 more Smart Citations